2010
DOI: 10.1002/ejoc.201000733
|View full text |Cite
|
Sign up to set email alerts
|

P‐Stereogenic Phosphorus Compounds: Effect of Aryl Substituents on the Oxidation of Arylmethylphenylphosphanes under Asymmetric Appel Conditions

Abstract: The effects of aryl ring substitution on the dynamic resolution of aryl(methyl)phenylphosphanes under asymmetric Appel reaction conditions have been studied. As expected, substitution at the ortho position strongly affects the degree of stereoselection that can be achieved. Unexpectedly, however, there was no variation of stereoselectivity with the elec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…It seems anomalous that the structure of the simple acetyl ylide 25 has not previously been reported. The pivaloyl ylide 26 is the first to be structurally characterised which is derived from a phosphine with three different groups and, since the phosphine involved is readily available in enantiomerically pure form by kinetic resolution, 42,43 this paves the way for formation of P-chiral ylides. The structure of 25 is shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems anomalous that the structure of the simple acetyl ylide 25 has not previously been reported. The pivaloyl ylide 26 is the first to be structurally characterised which is derived from a phosphine with three different groups and, since the phosphine involved is readily available in enantiomerically pure form by kinetic resolution, 42,43 this paves the way for formation of P-chiral ylides. The structure of 25 is shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl 4,4,4-Trifluoro-3-oxo-2-(triphenylphosphoranylidene)butanoate (43) Colourless crystals (53%) from ethyl acetate, mp 118-120 °C (Lit., 59…”
Section: 56mentioning
confidence: 99%
“…The pseudo-rotation of ligands at the P(V) atom leads to the formation of the most thermodynamically stable diastereomer of the halogen-phosphonium intermediate, which then turns into one diastereomer of the final product (Equation (69)) [89]. (69) Gilheany et al [91][92][93][94] carried out the asymmetric Appel reaction by oxidizing tertiary phosphines with polyhaloalkanes in the presence of chiral L-menthol. As a result, chiral phosphine oxides were obtained with a good ee.…”
Section: )mentioning
confidence: 99%
“…The dynamic kinetic resolution (DKR) of aryl(methyl) phenyl phosphines 48 was applied for the preparation of the corresponding enantioenriched tertiary phosphine oxides 49. [33] The key step of this methodology was the asymmetric oxidation under Appel conditions with (+)-menthol. In some cases, it was found that the substituent on an aryl ring strongly affects on the enantioselectivity of the reaction (Scheme 13).…”
Section: Asymmetric Synthesismentioning
confidence: 99%